Childhood Maltreatment Predicts Specific Types of Dysfunctional Attitudes in Participants With and Without Depression - Jugessur, Raj; Zhang, Yan; Qin, Xuemei; Wang, Mi; Lu, Xiaowen; Sun, Jinrong; Dong, Qiangli; Zhang, Liang; Liu, Jin; Ju, Yumeng; Liao, Mei; Wan, Ping; et al. (Frontiers in Psychiatry, 2021)
Background: Studies have shown a strong association between childhood maltreatment (CM) and Major Depressive Disorder (MDD). Dysfunctional attitudes (DAs) play a crucial role in the development of MDD. In this study, we aimed to investigate whether 1) DAs are associated with CM, 2) specific CM types predict specific types of DAs, and 3) higher childhood trauma counts predict more DAs. Methods: One hundred and seventy-one Major depressive disorder (MDD) participants and 156 healthy controls (HC) were enrolled for the study. CM was assessed retrospectively with the Childhood trauma questionnaire (CTQ). DAs were evaluated using the Chinese version of the dysfunctional attitude scale form A (C-DAS-A). A series of analyses, including multiple analyses of covariance and hierarchical regression analyses, were employed in this study to examine the hypotheses. Results: The proportion of CM was 60.2% in the MDD group and 44.2% in the HC group. The 2x2 ANCOVA results showed no interaction effect between CM and MDD on C-DAS-A total score. When the factor scores replaced the C-DAS-A total score, a similar trend was observed. Within the MDD group, emotional abuse (EA) predicted two forms of DAs: self-determination type and overall DAs; Physical neglect (PN) was predictive of attraction and repulsion type DAs. Higher childhood trauma counts significantly predicted more types of DAs in the MDD group. Conclusion: DAs are a trait feature of CM. EA and PN predict specific types of DAs in MDD patients. Higher CTCs predict more DAs in MDD patients.